THE SYNTHESIS OF N,O-CARBOXYMETHYL CHITOSAN-g- OLIGO(ASPARTIC ACID) AS CORROSION INHIBITOR ON CARBON STEEL AND SCALE INHIBITOR - JALIL BAARI (NIM:20516052), MUHAMAD
Corrosion on the inner surface of crude oil and natural gas pipelines due to fluid mixtures that produces CO2 co-insisted by the scale formation was the serious problem in oil and gas industry. Corrosion can cause thinning and leakage of pipeline, while scalling will reduce diameter of flowing pipe as well as blockage of some pipeline parts along the oil and gas transportation routes from oil wells to the treatment place, then it would be potentially causing financial loss and also environmental damage. Therefore, it is necessary to apply a method that can control corrosion rate as well as capable to prevent scale formation on that system, effectively and efficiently. Polymer compounds containing double bonds and heteroatoms are known to be effective as corrosion inhibitor because it can be complexing agent or chelating agent when those adhere on metal surfaces, it has good thermal stability and can cover larger metal surface areas. Chitosan is one of the biopolymers that can be used as a corrosion inhibitor, but it has low solubility in water. Increasing the solubility of chitosan in water can be done by carboxymethylation reaction. Meanwhile, oligosuccinimide (OSI) is an intermediate of oligoaspartic acid that was known to be effective as a scale inhibitor. In this study, N,O-carboxymethyl chitosan (N,O-KMK) and oligosuccinimide were synthesized. Then, it followed by grafting onto copolymerized reactions between N,O-KMK and OSI to produce N,O-carboxymethyl chitosan-g-oligo(aspartic acid) or N,O-KMK-g-OASP which has double functions both as corrosion inhibitor and scale inhibitor. The structure analysis of precursors and copolymer was performed by Fourier Transform Infrared (FTIR), Nuclear Magnetic Resonance (NMR) spectroscopy, and Liquid Chromatography-Mass Spectroscopy (LC-MS). The thermal stability of polymers was analyzed by thermogravimetric (TGA). Subsequently, the efficiency of corrosion inhibition was measured by Electrochemical Impedance Spectroscopy (EIS), potentiodinamic polarization (Tafel) and weight loss test methods in 1% (w/v) NaCl solution saturated by CO2 gas, while scale inhibition was analyzed by static scale inhibition test. FTIR spectrum of N,O-KMK-g-OASP showed an increasing peak intensity in the wave number 1650 cm-1 from streching vibration in the bonding of amide carbonyl groups because more amide groups was formed after the copolymerization reaction. N,O-KMK and OSI were classified as mixed inhibitors. Each of them was effective enough to reduce corrosion rates at 35 oC and 25 oC respectively. N,OKMK still inhibited corrosion rate at 55 oC, but more rapidly coagulated, while OSI has higher inhibition efficiency at room temperature but it becomes ineffective at 55 oC. N,OKMK- g-OASP is classified as an anodic inhibitor, the efficiency of corrosion inhibition increased by increasing concentrations and temperature. N,O-KMK-g-OASP evaluation results as a CaCO3 scale inhibitor showed the inhibition efficiency up to 95.77% when the concentration amount 30 ppm. These results show that OSI, N,O-KMK and N,O-KMK-g- OASP are effective to reduce the corrosion rate on carbon steels in 1% (w/v) NaCl solution saturated by CO2 gas. In addition, N,O-KMK-g-OASP also showed effective performance as a CaCO3 scale inhibitor.